Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Ren, Qiang; Liu, Yansong; Wang, Ran; Nan, Feng; Wang, Jianfeng; Diao, Xinyuan; Chen, Zifei; Yu, Fei; Zhang, Chuangzheng; Zhao, Ruixiang; Zheng, Hua; Zhu, Xiao-Hua (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans, however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy-Kuroshio interactions based on large-scale in-situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018-2019 (12 deployed east of Taiwan within a 3×4 grid) were used to reveal the three-dimension structure of mesoscale eddies and their interaction with Kuroshio. The results strengthen (weaken) the tilt of the pycnocline and also caused the deeper (shallower) pycnocline at eastern Taiwan when anticyclonic (cyclonic) interaction with Kuroshio,which result in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downwards (upwards) movement at the centre of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for the further research of energy exchange during eddy Kuroshio interactions.